Población penitenciaria con discapacidad en el sistema jurídico peruano (Tema Central) - Seminario Hurtado, Nuccia (2024)
This article aims to elucidate the legal situation of the incarcerated population with disabilities in Peru. To achieve this, a study is conducted on individuals with disabilities within the Peruvian penal reality, followed by an analysis of the corresponding legal framework and local progress and challenges regarding their rights. Proposed improvements to the prison system aim to enhance accessibility, availability, acceptability, and inclusion in correctional facilities. These enhancements involve treating vulnerability with humane considerations, replacing the traditional rehabilitative policy as the primary purpose of punishment. Additionally, the establishment of penal execution courts is proposed for processing penitentiary benefits. A qualitative methodology with a documentary design and descriptive scope is employed. As a key finding, given the extreme vulnerability of the incarcerated population with disabilities in Peru, there is a highlighted need to imbue the prison sentence with distributive political foundations, aligning with international Human Rights standards prioritizing the reduction of structural barriers. In this regard, the adoption of a humane treatment policy and the implementation of penal execution courts are deemed viable measures to reduce the vulnerability of inmates with disabilities and promote the respect of their fundamental rights.